2022
DOI: 10.3389/fragi.2022.736835
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Attenuates Inflammatory Responses and Enhances Antibody Production in an Acute Pneumonia Model of Streptococcus pneumoniae

Abstract: Metformin may potentially reverse various age-related conditions; however, it is unclear whether metformin can also mitigate or delay the deterioration of immunological resilience that occurs in the context of infections that are commonly observed in older persons. We examined whether metformin promotes the preservation of immunological resilience in an acute S. pneumoniae (SPN) infection challenge in young adult mice. Mice were fed metformin (MET-alone) or standard chow (controls-alone) for 10 weeks prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Metformin is the first-line therapy for T2D and most of the diabetes patients might have taken metformin. Metformin has been shown to reduce the risk of many bacterial and viral infections including zika virus ( 21 ), dengue virus ( 21 ), Hepatitis C virus ( 22 ), Streptococcus pneumoniae ( 23 ) and PTB ( 24 ). The use of metformin in many of the patients with T2D might have modified and attenuated the positive association between T2D and PTB.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is the first-line therapy for T2D and most of the diabetes patients might have taken metformin. Metformin has been shown to reduce the risk of many bacterial and viral infections including zika virus ( 21 ), dengue virus ( 21 ), Hepatitis C virus ( 22 ), Streptococcus pneumoniae ( 23 ) and PTB ( 24 ). The use of metformin in many of the patients with T2D might have modified and attenuated the positive association between T2D and PTB.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that diabetes mellitus is a protective factor against acute respiratory distress syndrome (ARDS), probably due to a lowering effect on cytokine storm produced by diabetes in this context 48 , 49 . Furthermore, a recent pre-clinical study suggests a potential protective effect of metformin, the most used oral antidiabetic drug, against severe forms of pneumonia due to Streptococcus pneumoniae 50 . Taken together, the above-mentioned findings might furnish a possible interpretative key of the negative association between diabetes mellitus and the incidence of nosocomial pneumonia found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin has direct anti-inflammatory action via inhibition of nuclear factor κB (NFκB) via AMPK-dependent and independent pathways ( Saisho, 2015 ) and has been shown to suppress pro-inflammatory cytokines ( Zhou et al, 2016 ; Giusti et al, 2022 ). Studies have also shown that metformin can improve metabolic parameters such as hyperglycemia, insulin resistance, and atherogenic dyslipidemia ( Lee et al, 2022 ) that contribute to inflammatory processes. In addition, metformin can modulate the gut microbiome ( Cabreiro et al, 2013 ; Sun et al, 2018 ; Pryor et al, 2019 ), further reducing inflammation and improving metabolism.…”
Section: Metformin Mechanisms and Aging Biologymentioning
confidence: 99%